'One Health’ - the Rosetta stone for 21st century health and health providers - Bruce Kaplan, DVM; Mary Echols, DVM, MPH (Veterinaria Italiana, 2009)
The transformation and implementation of the One Health concept into a broad-spectrum institutional approach for health, health care and environmental health for humans and animals in society will require a paradigm shift. This represents a worldwide strategic scientific revolution vis-à-vis the status quo of traditional science-based activities of past and current medical and health endeavours that are frequently limited to provincial ‘turf’-domains. It means expanding interdisciplinary collaborations and communications into an all inclusive utilisation of co-equal participation among physicians, veterinarians and a host of other health scientist professionals. The resulting synergism will ‘advance health care for the 21st century and beyond by accelerating biomedical research discoveries, enhancing public health efficacy, expeditiously expanding the scientific knowledge base, and improving medical education and clinical care’. Untold millions of lives will be protected and saved in this generation and in those of the future.